Z-type ternary heterojunction BiOCl / CQD / C3N4 composite material as well as preparation method and application thereof

By introducing carbon quantum dots between BiOCl and g-C3N4, the Z-type ternary heterojunction BiOCl/CQD/C3N4 composite material was designed, and the problem of interfacial resistance was solved, the photocatalytic performance was limited, and the effect of efficient removal of tetracycline hydrochloride was achieved, and good stability and repeatability were demonstrated.

CN119857514APending Publication Date: 2025-04-22INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510000611.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing interface resistance between BiOCl and g-C3N4 limits its photocatalytic performance, making it difficult to effectively remove organic pollutants such as tetracycline hydrochloride in the environment.

Method used

By introducing carbon quantum dots (CQD) as charge carrier mediator, Z-type ternary heterojunction BiOCl/CQD/C3N4 composite materials are designed to reduce interface resistance and improve electron transfer efficiency.

Benefits of technology

The photocatalytic performance is significantly improved, the absorption range of visible light and the adsorption capacity of pollutants are enhanced, the degradation efficiency of tetracycline hydrochloride is improved, and the catalyst has good stability and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857514A_ABST
    Figure CN119857514A_ABST
Patent Text Reader

Abstract

The invention discloses a Z-type ternary heterojunction BiOCl / CQD / C3N4 composite material and a preparation method and application thereof.The preparation method comprises the steps that bamboo-based carbon quantum dots (CQD) are prepared firstly, then the CQD / BiOCl composite material is prepared through a hydrothermal method, and finally a target product is prepared through the hydrothermal method and a photo-assisted method. The bamboo-based carbon quantum dots have excellent electron transmission performance due to nitrogen and silicon elements naturally contained in bamboo wood, so that the electron transmission performance of the catalytic material is remarkably improved. The successful preparation of the Z-type heterojunction in BiOCl / CQD / C3N4 gives full play to the advantages of the positive valence potential of BiOCl and the negative conduction potential of CN, and overcomes the limitation that the charge recombination rate of electrons and holes of BiOCl and C3N4 is too high. The prepared composite material has a good catalytic degradation effect on organic pollutants such as tetracycline hydrochloride in waste water, can be repeatedly used, and has wide popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and specifically relates to a Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 Composite material and preparation method and application thereof. Background Art

[0002] Tetracycline hydrochloride is a widely used tetracycline antibiotic. Due to its long-term use, a large amount of residues have been discharged into the environment, especially in water bodies and soil. These residues are not only difficult to degrade naturally, but also bioaccumulate, posing a significant threat to ecosystems and human health. At present, the methods for removing tetracycline hydrochloride from the environment include physical, chemical and biological treatment technologies, but these methods have problems such as low treatment efficiency, complex operation and secondary pollution. Therefore, there is an urgent need to develop more efficient and sustainable treatment technologies.

[0003] Bismuth oxychloride (BiOCl) has attracted extensive attention due to its excellent photocatalytic efficiency and stable chemical structure. 2 O 2 ]²⁺ layers are interlaced with [Cl]⁻ layers, which endows BiOCl with good potential in catalytic degradation of pollutants. However, its practical application is restricted by factors such as limited visible light absorption range, low electron-hole separation efficiency, and reliance on a single active substance. 3 N 4 As a metal-free two-dimensional layered semiconductor, gC has also received extensive attention in the field of photocatalysis in recent years due to its non-toxicity, easy synthesis, tunable electronic properties and strong visible light absorption ability. 3 N 4 Further modification can not only optimize its band structure, but also increase its reduction potential, thereby promoting the generation of reactive species (such as superoxide radicals·O 2 ⁻) Recent studies have shown that the generation of BiOCl and gC 3 N 4 The coupling can significantly improve the photocatalytic activity of the composite material, giving full play to the positive valence band (VB) potential of BiOCl and gC 3 N 4 However, BiOCl and gC 3 N 4 The interface resistance between them still limits the charge transfer efficiency, thus affecting the overall performance of the heterojunction. Summary of the invention

[0004] In order to solve the problem of BiOCl and gC 3 N4 Due to the problem that interface resistance affects its performance, studies have found that introducing charge carrier mediators, such as carbon quantum dots (CQDs), can effectively alleviate the interface resistance in Z-type heterojunctions. CQDs have been shown to be an effective electron mediator that can accelerate electron migration and inhibit charge recombination due to their conjugated π structure and rich oxygen-containing functional groups. Bio-derived CQDs have become a promising photocatalyst due to their unique biocompatibility, high water solubility, non-toxicity, and excellent photoelectric properties. Bamboo, as a rapidly renewable resource rich in silicon and nitrogen, has become a natural and sustainable precursor for the synthesis of N- and Si-doped CQDs. The integration of bamboo-derived CQDs into photocatalytic systems not only highlights the application potential of renewable materials in advanced technologies, but also helps to develop sustainable and high-performance photocatalysts. By combining BiOCl and gC 3 N 4 The introduction of CQDs and the design of a sophisticated interface to promote electron transfer significantly improved the photocatalytic performance, providing a new paradigm for improving the photocatalytic efficiency of catalysts by forming a Z-type heterojunction.

[0005] The purpose of the present invention is to provide a Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 A composite material and a preparation method and application thereof are provided to solve the problems in the prior art.

[0006] To achieve the above object, the technical solution adopted by the present invention is: The first object of the present invention is to provide a Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 The method for preparing a photocatalytic composite material comprises the following steps: The CQD solution was prepared by a hydrothermal method: the bamboo pulp preparation waste was crushed and sieved to collect bamboo powder with a particle size greater than 100 mesh. After the bamboo powder was evenly mixed with distilled water, it was placed in a polytetrafluoroethylene-lined stainless steel hydrothermal kettle for hydrothermal reaction. After the reaction was cooled to room temperature, it was filtered, the lower brown-yellow liquid was collected, and further purified by dialysis to finally obtain a CODs solution. Preferably, the mass ratio of the bamboo powder to water is 1:20~1:60, and the filtration uses a 0.22-0.45μm filter membrane; the dialysis uses a 500-2000Da molecular weight dialysis bag, and the dialysis time is 24~48 hours. As a preferred technical solution, the temperature of the hydrothermal reaction is 100-200°C and the time is 10-20 hours. Further preferably, the temperature of the hydrothermal reaction is 200°C and the time is 16 hours to obtain the best performance. The CQD / BiOCl composite photocatalyst is prepared by a hydrothermal method: a bismuth salt is dissolved in ethylene glycol (EG) to obtain a dispersion A; a chloride salt is dissolved in deionized water to form a solution B. The CQD solution is uniformly mixed with the B solution, and the mixed solution is slowly added to the A solution to form a uniform white suspension. Then it is transferred to a stainless steel hydrothermal kettle of polytetrafluoroethylene for hydrothermal reaction. After the reaction is completed, the obtained material is cooled, separated, washed and dried to finally obtain a CQD / BiOCl composite photocatalytic material; the chloride salt is sodium chloride or potassium chloride; the bismuth salt is bismuth nitrate, bismuth sulfate or bismuth chloride; as a preferred technical solution, the atomic molar ratio of bismuth and chlorine in the bismuth salt and the bromide salt is 1:1. The temperature of the hydrothermal reaction is 140-200°C and the time is 10-20 hours; further preferably, the temperature of the hydrothermal reaction is 160°C and the time is 10 hours.

[0007] (3) Preparation of C by secondary calcination 3 N 4 : Melamine was placed in a dry ceramic crucible with a lid and placed in a tube furnace for the first calcination. After heating, the resulting pale yellow solid was cooled to room temperature and further ground to obtain a fine powder. Subsequently, the fine powder was placed in a dry ceramic crucible without a lid and placed in a tube furnace for the second calcination, and finally cooled to room temperature to collect C 3 N 4 Nanosheets; preferably, the first calcination temperature is 400-600°C, and the time is 2-6 hours; the second calcination temperature is 450-550°C, and the time is 2-6 hours.

[0008] (4) Preparation of BiOCl / CQD / C by hydrothermal and photo-assisted methods 3 N 4 Ternary heterojunction composite materials: C 3 N 4 The nanosheets were dispersed in deionized water and sonicated until completely dissolved to obtain C 3 N4 The CQD / BiOCl composite material was mixed with C 3 N 4 The solution was mixed under visible light to make it tightly combined. The mixed solution was placed in a 60°C oven for drying, and finally BiOCl / CQD / C 3 N 4 Preferably, the CQD / BiOCl composite material is combined with C 3 N 4 The solution was mixed under visible light for 1-16 hours; the CQD / BiOCl composite material and C 3 N 4 C in solution 3 N 4 The mass ratio is 10:(1-3) The second object of the present invention is to provide a Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 A photocatalytic composite material, which is obtained by the preparation method in the first object mentioned above.

[0009] The third object of the present invention is to provide a Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 Application of photocatalytic composite materials. The photocatalytic material can be effectively used to catalytically degrade pollutants in wastewater, and is particularly suitable for degrading organic pollutants such as tetracycline hydrochloride in wastewater.

[0010] The present invention has the following beneficial effects: The present invention uses bamboo pulp preparation waste to prepare quantum dots, and then successfully synthesizes Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 Composite materials. Bamboo-based carbon quantum dots have excellent electron transport properties due to the nitrogen (N) and silicon (Si) elements naturally contained in bamboo, which significantly improves the electron transport performance of the catalytic material. In addition, the influence of quantum effects greatly increases the absorption range of visible light by the catalytic material. The porous structure of CQD provides a higher specific surface area and rich pore structure, which promotes the adsorption of pollutants and thus accelerates the rate of photocatalytic reactions. Carbon nitride prepared by secondary calcination has higher purity and a more stable π-conjugated system, which enhances the conductivity and catalytic performance of the material. Secondary calcination also increases the specific surface area of ​​carbon nitride. BiOCl / CQD / C 3 N 4 The successful preparation of the Z-type heterojunction fully utilized the positive valence band (VB) potential of BiOCl and the C 3 N 4 The advantage of negative conduction band (CB) potential overcomes the3 N 4 The limitation of high electron and hole recombination rate. The Z-type heterojunction prepared by hydrothermal method and light-assisted method has stable structure, significant catalytic effect, and can be reused, which has broad prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 SEM images (ab) and TEM images (c) of 5CB-CN-10-2; Figure 2 EPR diagrams of 5CB-CN-10-2 and BiOCl; Figure 3 BET diagram of 5CB-CN-10-2 and BiOCl; Figure 4 5CB-CN-10-2, C 3 N 4 and XPS spectra of CQDs; Figure 5 The cyclic degradation experimental diagram of 5CB-CN-10-2 (a) and the XRD diagram before and after the cycle (b). DETAILED DESCRIPTION

[0012] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0013] In addition, unless otherwise specified, the preparation processes in the following examples are all conventional means in the prior art, and therefore, no further details are given. The raw materials and reagents used in the following embodiments are all commercially available products.

[0014] Example 1 A Z-type ternary heterojunction BiOCl / CQD / C 3 N 4 The method for preparing a photocatalytic composite material comprises the following steps: (1) A method for preparing CQDs, comprising the following steps: Bamboo pulp preparation waste was used as raw material, which was crushed and sieved to obtain bamboo powder with a particle size greater than 100 mesh. 1.5 g of bamboo powder was evenly mixed with 60 mL of distilled water and placed in a polytetrafluoroethylene stainless steel hydrothermal autoclave, heated at 200 ℃ for 16 hours, cooled to room temperature, and filtered through a 0.22 μm filter membrane to collect the lower brown-yellow liquid. The liquid was placed in a dialysis bag with a molecular weight of 1000 Da and dialyzed for 48 hours. The obtained solution was the CQD solution, and the prepared product was named CQD.

[0015] (2) A method for preparing a CQD / BiOCl composite photocatalyst, comprising the following steps: 3mmolBi(NO 3 ) 3 ·5H 2 O was dissolved in 30 mL of ethylene glycol (EG), first subjected to ultrasonic treatment for 30 min, and then stirred vigorously for 30 min to obtain dispersion A; 3 mmol NaCl was dissolved in 25 mL of deionized water to form solution B. 5 mL of CQD solution with a concentration of 0.15 mg / mL was uniformly mixed in solution B, and then the mixed solution was slowly added dropwise to dispersion A to form a uniform white suspension. The suspension was transferred to a stainless steel hydrothermal reactor containing polytetrafluoroethylene for hydrothermal reaction at 160 °C for 10 hours. After the reaction, the obtained material was cooled to room temperature, washed several times with deionized water and ethylene glycol, and finally placed in an oven for drying. The final product was labeled 5CB.

[0016] (3)C 3 N 4 The method for preparing the nanosheet comprises the following steps: Weigh 12 g of melamine, place it in a dry ceramic crucible with a lid, and place it in a tube furnace for the first calcination. Set the heating conditions to increase the temperature from 20 ° C to 550 ° C at a rate of 5 ° C / min, and keep it at 550 ° C for 4 hours. After the heating is completed, wait for the obtained light yellow solid to cool to room temperature and further grind it to obtain a fine powder. Subsequently, the ground fine powder is placed in a dry ceramic crucible without a lid, and placed in a tube furnace for secondary calcination. Set the conditions to heat from 20 ° C to 500 ° C at a rate of 5 ° C / min, and keep it warm for 4 hours. After heating, cool to room temperature and collect C 3 N 4 Nanosheets.

[0017] (4) A BiOCl / CQD / C 3 N 4 A method for preparing a Z-type ternary heterojunction comprises the following steps: 100 mg C 3 N 4 The nanosheets were dispersed in 100 mL of deionized water and ultrasonicated until completely dissolved to obtain C 3 N 4 Weigh 50 mg of CQD / BiOCl composite material and 10 mL of C 3 N 4 The solution was mixed under visible light for 2 hours, and the mixed solution was placed in a 60°C oven for drying to obtain BiOCl / CQD / C 3 N 4Z-type ternary heterojunction, the prepared product is labeled 5CB-CN-10-2.

[0018] Comparative Example 1 Preparation of pure BiOCl: 3mmolBi(NO 3 ) 3 ·5H 2 O was dissolved in 30 mL of ethylene glycol (EG), first subjected to ultrasonic treatment for 30 min, and then stirred vigorously for 30 min to obtain dispersion A; 3 mmol NaCl was dissolved in 25 mL of deionized water to form solution B. Solution B was slowly added dropwise to dispersion A to form a uniform white suspension. The suspension was transferred to a stainless steel hydrothermal reactor containing polytetrafluoroethylene for hydrothermal reaction at 160 °C for 10 hours. After the reaction, the obtained material was cooled to room temperature, washed several times with deionized water and ethylene glycol, and finally dried in an oven to obtain pure BiOCl.

[0019] Example 2-3 Compared with Example 1, the difference between Example 2-3 is that in step (4), C 3 N 4 The amount of solution added was different, 5 mL and 15 mL respectively, and the other conditions were the same as in Example 1. The prepared products were named 5CB-CN-5-2 and 5CB-CN-15-2 respectively.

[0020] Embodiment 4-6 Compared with Example 1, the difference between Examples 4-6 lies in the different mixing times under visible light in step (4), that is, under visible light irradiation conditions, the CQD / BiOCl composite material and the C 3 N 4 The mixing time of the solutions was 1 hour, 8 hours and 16 hours respectively. The other conditions were the same as those in Example 1. The prepared products were named 5CB-CN-10-1, 5CB-CN-10-8 and 5CB-CN-10-16 respectively.

[0021] Example 7 Compared with Example 1, the difference in Example 7 is that in step (4), the CQD / BiOCl composite material and C 3 N 4 The binding modes between solutions are different. Specifically, 50 mg of CQD / BiOCl composite was weighed and mixed with 10 mL of C 3 N 4 The solution was mechanically stirred for 2 hours in the dark. Other conditions were the same as in Example 1. The product was named 5CB-C 3 N 4。

[0022] Photocatalytic performance test Degradation of Tetracycline Hydrochloride The products prepared in the above-mentioned embodiments and comparative examples were respectively tested for pollutant degradation performance, and the method is as follows: 50 mg of the above photocatalytic materials were added to 150 mL of 30 mg / L tetracycline hydrochloride solution, stirred in the dark for 30 minutes to reach adsorption equilibrium, and then irradiated with a 300w Xe lamp (with a 420 nm cutoff filter) and reacted for 120 minutes under visible light irradiation. Samples were taken every 20 minutes, and the obtained samples were filtered through a 0.22 μm filter membrane. The supernatant was tested for the content of tetracycline hydrochloride by a spectrophotometer, and the test wavelength was 357 nm. The results are shown in Table 1.

[0023] Table 1 Degradation rate of tetracycline hydrochloride by products prepared in various embodiments and comparative examples

[0024] As can be seen from Table 1, pure BiOCl performs poorly in removing tetracycline hydrochloride. Under dark conditions, after 30 minutes of adsorption, the adsorption rate was only 5.6%, and the removal rate reached 20.8% after 120 minutes of illumination. After adding quantum dots, the adsorption effect and photodegradation effect of the 5CB composite catalyst were significantly improved. This proves that the porous structure of quantum dots is conducive to the adsorption of pollutants. At the same time, the natural elements unique to quantum dots effectively enhance the electron transport performance of quantum dots, thereby improving the photocatalytic activity of quantum dots / BiOCl. In the composite material BiOCl / CQD / C 3 N 4 The significant improvement in the photocatalytic effect is attributed to the successfully prepared Z-type heterojunction. This is because the successful preparation of the Z-type heterojunction significantly improves the electron transmission efficiency and fully utilizes the positive valence band (VB) potential of BiOCl and C 3 N 4 The advantage of negative conduction band (CB) potential effectively overcomes the 3 N 4 The electron and hole recombination rate is too high. Too long mixing time will destroy the combination between BiOCl and CQD, and C 3 N 4 Excessive addition of C 3 N 4 The nanosheets blocked the pores of 5CB, thus affecting the adsorption effect. 3 N 4The adsorption and degradation effects of 5CB-CN-10-2 are significantly inferior to those of 5CB-CN-10-2 prepared by the light-assisted method. This is because the surface state of carbon nitride is activated under light conditions, which increases its ability to accept electrons and improves its catalytic activity. In contrast, the mechanical mixing method lacks light activation and efficient electron transfer mechanisms, resulting in limited catalytic performance.

[0025] Material characterization In order to study the microstructure of the composite material 5CB-CN-10-2, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were performed. Figure 1 As shown. The quantum dots fit tightly onto the BiOCl surface, while C 3 N 4 Surrounding 5CB. Figure 1 Figure a shows the close combination of the three, proving that 5CB and C 3 N 4 A strong interaction occurs, which promotes the increase of oxygen vacancy content ( Figure 1 TEM image ( Figure 1 The lattice fringes shown in Figure c) are 0.220 nm, 0.367 nm, and 0.325 nm, respectively. These fringes correspond to the (100) plane of CQD, the (002) plane of BiOCl, and the (003) plane of CQD. 3 N 4 The (002) plane of the composite further verifies the successful preparation of the ternary heterostructure, in which the CQDs act as electron bridges at the interface, facilitating efficient charge carrier transfer between the composite components.

[0026] like Figure 2 As shown, all samples exhibit a characteristic single Lorentzian line centered at g = 0.2003, indicating that the oxygen vacancies capture unpaired electrons. The number of oxygen vacancies is proportional to the relative intensity of the EPR signal peak. The relative intensity of the EPR peak of 5CB-CN-10-0 is significantly higher than that of BiOCl, successfully proving the generation of oxygen vacancies in the heterojunction.

[0027] Figure 3 The adsorption isotherms, specific surface areas, and pore sizes of 5CB-CN-10-2 and BiOCl are shown. Both exhibit type IV isotherms with H3 hysteresis loops, indicating the presence of a mesoporous structure. The specific surface area of ​​5CB-CN-10-2 is 37.77 m 2 / g, about BiOCl (15.70 m 2 / g) and the pore size of 5CB-CN-10-2 is larger than that of BiOCl. These features promote the diffusion of pollutants and active free radicals, thereby enhancing the photocatalytic degradation activity. The increased specific surface area combined with the porous structure provides abundant active sites for adsorption and photocatalytic reactions, ultimately improving the photocatalytic performance.

[0028] like Figure 4 As shown, the elemental composition of the composite material was deeply analyzed using XPS technology. Figure 4 Figure a shows that 5CB-CN-10-2 has three C 1 s peaks at 284.78 eV, 286.54 eV, and 288.71 eV, corresponding to CC, CO-Bi, and C=O, respectively. The formation of CO-Bi indicates the existence of a chemical bond between CQD and BiOCl. Figure 4 In Figure b, peaks at 396.39 eV, 399.76 eV, and 400.90 eV are observed, which correspond to C=NC, NC 3 and π excited states. The π excitation peak of 5CB-CN-10-2 is significantly enhanced, indicating that 5CB-200-16 and C 3 N 4 There is a strong π conjugation between them. In addition, 3 N 4 In comparison, the N1s peak of 5CB-CN-10-2 shifts to a lower binding energy. Figure 4 As shown in Figure bc, Bi of 5CB-CN-10-2 4f and Cl 2p The peak shifts to a higher binding energy, indicating that the electron density of BiOCl decreases. Combined with the N spectrum analysis, it can be inferred that in the 5CB-CN-10-2 composite material, electrons are transferred from BiOCl to CQDs. 3 N 4 , forming a Z-type heterojunction, and CQD plays a key role in promoting the electron transfer process.

[0029] The reusability of the 5CB-CN-10-2 composite material was studied through a cycle experiment. After four cycles, the degradation efficiency of TCH remained at 82.4%, indicating that the catalyst has excellent stability and reusability. Figure 5 As shown, XRD analysis showed that the composition of the catalyst did not change significantly after four cycles; in addition, SEM images showed that the morphology and structure of 5CB-CN-10-2 remained intact, further demonstrating its good stability throughout the repeated photocatalytic process.

Claims

1. A method for preparing a Z-type ternary heterojunction BiOCl / CQD / C3N4 composite material, characterized in that: The following steps are involved: (1) Mix bamboo powder and water evenly and perform hydrothermal reaction. After the reaction is completed and cooled to room temperature, filter and collect the brown-yellow liquid at the bottom layer, and further purify it by dialysis to obtain a CQD solution; (2) dissolving bismuth salt in ethylene glycol to obtain dispersion A; dissolving chloride salt in water to form solution B; mixing CQD solution and solution B to obtain a mixed solution, and then adding the mixed solution to dispersion A to form a uniform white suspension, and after sufficient mixing, transferring to a hydrothermal kettle for hydrothermal reaction; after the reaction is completed, the obtained material is cooled, separated, washed and dried to obtain a CQD / BiOCl composite material; (3) Using melamine as raw material, C3N4 nanosheets were prepared by secondary calcination; (4) Dissolving C3N4 nanosheets in water to obtain a C3N4 solution; mixing the CQD / BiOCl composite material with the C3N4 solution under visible light to allow them to be tightly combined; and drying the mixed solution after standing to finally obtain a BiOCl / CQD / C3N4 composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the bamboo powder to water is 1:20-1:

60.

3. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 100-200° C. and the time is 10-20 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the chloride salt is sodium chloride or potassium chloride; and the bismuth salt is bismuth nitrate, bismuth sulfate or bismuth chloride.

5. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 140-200° C. and the time is 10-20 hours.

6. The preparation method according to claim 1, characterized in that: In step (3), the specific process of preparing C3N4 nanosheets by secondary calcination using melamine as raw material is as follows: placing melamine in a dry ceramic crucible with a cover, placing it in a tubular furnace for the first calcination, and waiting for the obtained light yellow solid to cool to room temperature, and obtaining a fine powder after grinding; then, placing the fine powder in a dry ceramic crucible without a cover, and placing it in a tubular furnace again for the second calcination, and finally cooling to room temperature to obtain C3N4 nanosheets; the temperature of the first calcination is 400-600°C, and the time is 2-6 hours; the temperature of the second calcination is 450-550°C, and the time is 2-6 hours.

7. The preparation method according to claim 1, characterized in that: In step (4), the CQD / BiOCl composite material and the C3N4 solution are mixed under visible light for 1-16 hours.

8. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of the CQD / BiOCl composite material to C3N4 in the C3N4 solution is 10:(1-3).

9. A Z-type ternary heterojunction BiOCl / CQD / C3N4 composite material, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the Z-type ternary heterojunction BiOCl / CQD / C3N4 composite material as claimed in claim 9 in degrading pollutants in wastewater.